GENERATIVE AI-ENHANCED GAME-BASED LEARNING FOR CREATIVE SKILL DEVELOPMENT IN ELEMENTARY STUDENTS - Yani Fitriyani; Sena Aditia Apriadi; Sulistiani; Ndaru Mukti Oktaviani (Universitas Majalengka, 2025)
Student creativity in Indonesia remains a serious problem that requires special attention, with the 2022 PISA survey identifying only 5% of students achieving high creativity. Science learning is also still limited in integrating technology to develop creativity, even though this ability is a very important competency in the digital era. This study aims to develop Game-based Learning (GBL) with Generative AI (Gen AI) to improve the creativity of 5th grade elementary school students. The research method uses Research and Development (RnD) with the ADDIE model including five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 20 5th grade students of SDN Kutakembaran 1. GBL was developed with the ChatGPT-3.5 API to produce adaptive learning content. ChatGPT-3.5 works by analyzing student responses, automatically generating game scenarios, questions, and challenges tailored to the individual student's ability level. This development is enriched with West Javanese cultural elements such as folklore, traditions, and local contexts to increase the relevance of learning. The research instruments include expert validation (n=5), a creativity rubric that measures four indicators (fluency, flexibility, originality, elaboration) through problem-solving tasks, and observation of student engagement using a Likert scale that records active participation. The expert validation results showed a feasibility score of 77.50 (good category) with an Aiken's V coefficient of 0.813 (p<0.001). Implementation resulted in a significant increase in the creativity dimensions: fluency (23%, p<0.05), flexibility (31%, p<0.01), originality (28%, p<0.05), and elaboration (19%, p<0.05). Student engagement reached an average of 78.60 with 80% positive responses, while technology acceptability reached 83.45%. The culture-based GBL-GenAI media has proven effective in developing student creativity and making a significant contribution to innovation in science learning for the transformation of Indonesian basic education.